A prospective 3-year follow-up trial of implantation of two trabecular microbypass stents in open-angle glaucoma - Donnenfeld ED (Dove Medical Press, 2015)
Eric D Donnenfeld,1 Kerry D Solomon,2 Lilit Voskanyan,3 David F Chang,4 Thomas W Samuelson,5 Iqbal Ike K Ahmed,6 L Jay Katz7 1Ophthalmic Consultants of Long Island, Rockville Centre, NY, 2Carolina Eyecare Physicians, Mt Pleasant, SC, USA; 3S.V. Malayan Ophthalmology Centre, Yerevan, Armenia; 4Altos Eye Physicians, Los Altos, CA, 5Minnesota Eye Consultants, Minneapolis, MN, USA; 6University of Toronto, Toronto, ON, Canada; 7Wills Eye Hospital, Jefferson Medical College, Philadelphia, PA, USA Purpose: To evaluate 3-year safety and intraocular pressure (IOP) following two trabecular microbypass stents in phakic and pseudophakic subjects with open-angle glaucoma (OAG) not controlled on preoperative medication. Patients and methods: In this prospective pilot study, phakic or pseudophakic subjects with OAG and IOP between 18 mmHg and 30 mmHg on one preoperative topical ocular hypotensive medication underwent medication washout. Thirty-nine qualified subjects with preoperative unmedicated IOP ≥22 mmHg and ≤38 mmHg received two stents. Postoperative examinations were scheduled at Day 1, Week 1, Months 1, 3, 6, and 12, and semiannually through Month 60. Ocular hypotensive medication was considered if postoperative IOP exceeded 21 mmHg. IOP, medication use, and safety were assessed at each visit. Subject follow-up through Month 36 was completed. Results: Thirty-six eyes (92.3%; 95% confidence interval [CI] 79.1%, 98.4%) achieved the primary efficacy end point of Month 12 reduction in IOP ≥20% from baseline (unmedicated IOP) without ocular hypotensive medication. Four subjects required medication during the Month 36 follow-up period. Mean IOP at 36 months for subjects not taking medication was 15.2 mmHg. At 36 months, subjects sustained mean IOP decrease of 9.1±2.7 mmHg (95% CI 8.0 mmHg, 10.14 mmHg), or 37% IOP reduction, from unmedicated baseline IOP. Compared to preoperative medicated IOP, subjects had mean reduction at Month 36 of 5.5±2.7 mmHg (95% CI 4.5 mmHg, 6.6 mmHg), or 26% reduction. Both measures of IOP reduction were highly significant (P<0.001). Other than one case of early postoperative hyphema that resolved at 1 week, no postoperative adverse events were attributed to stent implantation. Conclusion: In a pilot study, two trabecular microbypass stents to treat OAG subjects on one preoperative medication provided statistically significant, sustained, and safe reduction of IOP to ≤15 mmHg without medication through 36 months. Keywords: iStent, MIGS, OAG, intraocular pressure, IOP reduction